Coxiella-Like Endosymbiont of Rhipicephalus sanguineus Is Required for Physiological Processes During Ontogeny - Ben-Yosef, Michael; Rot, Asael; Mahagna, Mustafa; Kapri, Einat; Behar, Adi; Gottlieb, Yuval (Frontiers in Microbiology, 2020)
Obligatory hematophagous arthropods such as lice, bugs, flies and ticks harbor bacterial endosymbionts which are expected to complete missing dietary needs, and numerous genomics and some experimental evidences currently support this expectation. In hard ticks (Acari: Ixodidae) serval linages of bacterial symbionts have been documented, and very few were experimentally shown to be essential to some aspects of tick’s fitness, mostly showing reduction in reproductive fitness. In order to pinpoint the nature of interactions between hard ticks and their symbionts, we tested the effect of massive elimination of Coxiella-like endosymbionts (CLE) by antibiotics on the development and fitness of the brown dog tick (Rhipicephalus sanguineus). Administration of ofloxacin to repleted nymphs resulted in significant and acute reduction of the tick microbial community load and in CLE numbers in subsequent life stages (aposymbiotic ticks). As a result, aposymbiotic female, but not male nymphs, suffered a delayed post-feeding development. Additionally, aposymbiotic adult females needed a significantly prolonged feeding period in order to replete, and had reduced engorgement weight and lower capacity to produce eggs. As a result, aposymbiotic females, had a significantly reduced fecundity, as well as excessive reduced fertility. Eggs produced by aposymbiotic females were also free of CLE and resulting aposymbiotic larvae were unable to feed successfully. These results first demonstrate that the observed effects are due to CLE reduction and not due to antibiotic administration; and second, suggest that the contribution of CLE is not mandatory for oocyte development and embryogenesis, but is required during feeding in females where blood meal processing and tissue build up are prominent. Presumably, under these extreme physiological demands CLE contribute to Rh. sanguineus via supplementing essential micro and macronutrients. Further nutrient complementary studies are required to support this hypothesis.